Lords of wine and oile community and conviviality in the poetry of Robert Herrick - Connolly, Ruth.; Cain, Tom. (Oxford : Oxford University Press, 2011)
This is a book-length appraisal of the major 17th-century poet Robert Herrick. The collection reads his poetry in the context of his literary, musical, political, and religious affiliations and looks at how he both presents and constructs ideals of community through his work.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Herrick, Robert, -- 1591-1674 -- Criticism and interpretation; Communities in literature